PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DISCLOSURE DAN ENVIRONMENTAL PERFORMANCE RATING TERHADAP REAKSI INVESTOR - , I G N ADI SURYAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to examine the effect of environmental performance with Corporate Social Responsibility (CSR) Disclosure index andperformance of companies in the PROPER (Program Penilaian Peringkat Kinerja Perusahaan dalam Pengelolaan Lingkungan Hidup)on investor reaction to the cumulative abnormal return (CAR) proxies. This research is a quantitative model using multiple regression analysis to determine the direction and effect relationship dependent and independent variables. Samples used in the study was 25 manufacturing companies. Data takenfrom annual report 2009-2011 period manufacturing companies listed in Indonesia Stock Exchange and participated in PROPER since 2009. The data analysis technique and hypothesis testing using SPSS software version 20. The results showed that the environmental performance based on assessment of CSR disclosure index does not significantly affect to investor reaction. While the environmental performance based on the performance of the company on the PROPER significantly affect to investor reaction. However, taken together, the disclosure of performance of social environment companies able to significantly affect to investor reaction.